A comparative study on the hybrid teaching approach of basic business mathematics to pre-commerce students during MCO / Norazah Umar ... [et al.] - Umar, Norazah; Othman, Jamal; Kadar, Rozita; Ahmad, Nurhafizah (Unit Penerbitan JSKM, 2021)
Varieties of Teaching and Learning approaches have been applied among educators to the students during the Movement and Control Orders (MCO), COVID-19. Educators especially those who are teaching the mathematics subject need comprehensive and effective tools to make the students understand the concept and the students can do exercises with less face-to-face guidance or a normal conventional teaching approach. Teaching mathematics subjects especially to the Pre-Diploma students is very challenging because they are quite weak in mathematics fundamentals and coincidentally, they have to face the obstacle of teaching approach with Open Distance Learning (ODL) during MCO. Hence, creative and innovative methods are created and developed by educators to make teaching delivery effective and increase the learning curve or performance of mathematics among students. The ongoing and final assessment results are used to measure the performance of the students based on the teaching approach or model that has been practiced by the educators.